GREEN INVESTMENT BERBASIS BLUE CARBON: POTENSI PERDAGANGAN KARBON DAN KEBIJAKAN HUKUM DI KAWASAN PESISIR - M. Irfan Islami Rambe; Muhammad Natsir; Mustika Putra Rokan; M. Iqbal Asnawi; Fahman Urdawi Nasution (Jurnal Yuridis, 2025)
Indonesia’s coastal ecosystems have strategic potential to support green investment through blue carbon stored in mangroves, seagrass meadows, and coastal wetlands. This article examines the prospects of blue carbon–based carbon trading and the readiness of national and regional legal frameworks, focusing on Aceh. Using normative and exploratory approaches, it finds that despite existing regulations on sustainable investment and carbon economic value, blue carbon development is hindered by overlapping authorities, the absence of a national roadmap, limited technical guidance, and weak incentives and community involvement. The Aceh case shows adaptive initiatives through regional carbon regulation and mangrove restoration based on carbon credits. The article recommends regulatory harmonization, a national blue carbon roadmap, and strengthened fiscal incentives and community-based benefit-sharing mechanisms to support sustainable coastal development and climate mitigation goals.